Synthesis and characterization of isotopically-labeled silver, copper and zinc oxide nanoparticles for tracing studies in plants - Nath, Jayashree; Dror, Ishai; Landa, Premysl; Vanek, Tomas; Kaplan-Ashiri, Ifat; Berkowitz, Brian (Environmental pollution (Barking, Essex, 2018)
In parallel to technological advances and ever-increasing use of nanoparticles in industry, agriculture and consumer products, the potential ecotoxicity of nanoparticles and their potential accumulation in ecosystems is of increasing concern. Because scientific reports raise a concern regarding nanoparticle toxicity to plants, understanding of their bioaccumulation has become critical and demands more research. Here, the synthesis of isotopically-labeled nanoparticles of silver, copper and zinc oxide is reported; it is demonstrated that while maintaining the basic properties of the same unlabeled ("regular") nanoparticles, labeled nanoparticles enable more sensitive tracing of nanoparticles within plants that have background elemental levels. This technique is particularly useful for working with elements that are present in high abundance in natural environments. As a benchmark, labeled and unlabeled metal nanoparticles (Ag-NP, Cu-NP, ZnO-NP) were synthesized and compared, and then exposed in a series of growth experiments to Arabidopsis thaliana; the NPs were traced in different parts of the plant. All of the synthesized nanoparticles were characterized by TEM, EDS, DLS, ζ-potential and single particle ICP-MS, which provided essential information regarding size, composition, morphology and surface charge of nanoparticles, as well as their stability in suspensions. Tracing studies with A. thaliana showed uptake/retention of nanoparticles that is more significant in roots than in shoots. Single particle ICP-MS, and scanning electron micrographs and EDS of plant roots showed presence of Ag-NPs in particular, localized areas, whereas copper and zinc were found to be distributed over the root tissues, but not as nanoparticles. Thus, nanoparticles in any natural matrix can be replaced easily by their labeled counterparts to trace the accumulation or retention of NPs. Isotopically-labeled nanoparticles enable acquisition of specific results, even if there are some concentrations of the same elements that originate from other (natural or anthropogenic) sources.
Keywords: Nanoparticle uptake; kovové nanočástice; Nanoparticles; Silver; Zinc; Metal Nanoparticles; oxid zinečnatý; Isotopically labeled nanoparticles; měď; nanočástice; rostliny; Zinc Oxide; Copper; Copper nanoparticles; zinek; Silver nanoparticles; Zinc oxide nanoparticles; Plants; stříbro